Disability, and social and economic inclusion: who is in and out of the Australian National Disability Insurance Scheme?. Issue 3 (2nd July 2016) - Cebulla, Andreas; Zhu, Rong
ABSTRACT: A new National Disability Insurance Scheme is being trialled in Australia, following criticism of the fragmented and inequitable nature of existing disability supports (e.g. in the 2009 'Shut Out' report by the National People with Disabilities and Carer Council) and reform recommendations made by the Australian Government's Productivity Commission in 2011. The Insurance Scheme distinguishes between people living with disability who will be eligible for different types of supports: either mainly information about services provided in the community or direct supports and self-managed funding. Analysis of the categories highlights differences in socio-demographics, unmet need for help, and social and labour market inclusion. Unmet need for help was disproportionately prevalent among people with disability when compared to people not living with disability. A higher level of educational capital among people with most severe or profound disability, however, contributed to reduced levels of reported unmet need for some. Overlapping associations between disability, social characteristics and inclusion suggest that nuances in support needs be observed and interventions included that also support people with less severe disability.